Perancangan Sistem Informasi Medical Record pada Puskesmas Buhit - Simarmata, Ruth Elovani; Jamaluddin, Jamaluddin; Harianja, Eva Julia G. (Universitas Methodist Indonesia, 2024)
Along with the times, information technology is experiencing increasingly rapid changes in various fields. One that is used in the health sector is the medical record which is a record or file that contains the results of the patient's examination, the identity and history of the patient's illness and the results of the treatment that has been carried out. The problem that exists at the Buhit Health Center is that the system processing is still carrying out the process of recording manually into the patient's bookkeeping which results in problems that often arise at the Buhit Health Center, as well as the difficulty of processing files, such as patient data archive reports. In addition, the use of the existing system cannot guarantee the level of elasticity and is easily damaged, causing new problems such as difficulties in storing and backing up files. Medical history is also a problem in managing patient files, which are usually recorded in manual files, and stored where the patient receives treatment. The results of the problems above, the researcher designs and builds a medical record information system that functions to manage and store data and patient identity files.